2003
DOI: 10.1093/ejo/25.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory bone formation in young and old rats during tooth movement

Abstract: The aim of this study was to investigate compensatory lingual alveolar bone formation during tooth movement in young and old rats, using the vital bone marker tetracycline. Wistar male rats were separated into the following groups: 13-week-old rats without appliances (13C: control, n = 5), 60-week-old rats without appliances (60C: control, n = 5), 13-week-old rats with appliances (13E: experimental, n = 10), and 60-week-old rats with appliances (60E: experimental, n = 10). The upper first molars of the 13E and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…However, when a lingual molar movement was performed in young and old rats, the compensatory alveolar bone apposition was similar in both groups. 18 The age effect on orthodontic movement in rats was studied by Ren et al, 19 who reported faster mesiodistal initial tooth movement in juvenile rats than in adult rats. Once tooth movement had reached the linear phase, the rate of tooth movement did not differ between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, when a lingual molar movement was performed in young and old rats, the compensatory alveolar bone apposition was similar in both groups. 18 The age effect on orthodontic movement in rats was studied by Ren et al, 19 who reported faster mesiodistal initial tooth movement in juvenile rats than in adult rats. Once tooth movement had reached the linear phase, the rate of tooth movement did not differ between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Cells in the PDL are subjected to continuous mechanical strain and are forced to adapt to the new environment by synthesis and secretion of several cytokines and growth factors (Arai et al, 2010; Baba et al, 2011; Saito et al, 1991; Tsuge et al, 2016). As a result, reconstruction of the PDL and alveolar bone occur both in the tension and compression zones of the PDL (Nakamura et al, 2003; Shimpo et al, 2003; Takahashi et al, 2003, 2006). However, the detailed mechanisms of the cellular response in reconstruction of the PDL and alveolar bone have not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…However, Decker and Chen (2009) demonstrated good upper alveolar bone adaptation after 32 years of follow-up by case report. Shimpo et al (2003) thought that lingual alveolar bone height was maintained due to bone formation during moving first molar lingually in rats. Further research is necessary for alveolar bone dehiscence involving large incisor retraction and intrusion in adult patients with maximum anchorage.…”
Section: Introductionmentioning
confidence: 99%